Determinants of gini ratio: a case study of low gini ratio in Madura - Mahdi, Imam; Sulistyono, Setyo Wahyu (Universitas Widya Mataram, 2023)
One of the regencies on Madura Island, namely Sumenep, will be the regency with the lowest gini ratio in East Java Province in 2022. This research was conducted to analyze: 1) the effects of health, education, open unemployment rate, and poverty rate partially on the Gini ratio; 2) the effects of health, education, open unemployment rate, and poverty rate simultaneously on the Gini ratio in Madura Island. The research method was carried out using panel data regression. The results obtained using the CEM: 1) health, education, and poverty levels have a negative and not significant effect; 2) the open unemployment rate influences positively and significantly; 3) all independent variables simultaneously have a significant positive effect. The government can issue policies to reduce income inequality in the form of providing free health services, education and compulsory education scholarships, periodic job fairs, skills training for workers, and distribution of social assistance that is right on target.